EXISTENTIALISM: ABOUT “THE TRIAL OF THE ENTIRE UNIVERSE” - Xamraqulovna, Tursunova Nargiza (International Journal of Psychosocial Rehabilitation, 2020)
During the life of Kafka, only few of his stories were published in magazines and published in separate editions (“Observation”, 1913; “The judgment”, “Stoker”, 1913; “Metamorphosis”, 1916; “A Country Doctor”, 1919; “A Hunger Artist”, 1924). Despite this circumstance, already in 1915 he received one of the prestigious literary prizes in Germany named after T. Fontane. Kafka is a poet of sympathy and compassion. The writer’s best novel is “The Trial”, which describes the persecution of a person by the state machine for slander, in this “Kafka” absurdity, like in his other novel, “The Castle”, one sees a prediction of totalitarianism, which ultimately leads humanity to collapse. In the middle of twentieth century, existentialist philosophers appear on the scene of French literature, among which Jean-Paul Sartre and Albert Camus are recognized as the brightest representatives, writers who become the favorite objects of literary and historical-philosophical scientific research. The goal of Kafka, Sartre and Camus, the masters of the pen was one – the search for the meaning of life, the search for what contains the basic values and ideals of life: beauty, goodness, truth, justice, freedom.